A Comprehensive Review of Food Safety Culture in the Food Industry: Leadership, Organizational Commitment, and Multicultural Dynamics - Ashwini Sadashiv Pai; Swarna Jaiswal; Amit K. Jaiswal (Foods)
Food safety culture (FSC) has transitioned from a narrow compliance-based concept to a comprehensive organisational value that is essential for ensuring food safety. This review explores the pivotal roles of leadership, organisational commitment, and cultural diversity in shaping an effective FSC. It highlights how leadership style, particularly transformational leadership, can enhance employee engagement and foster a proactive safety culture. Additionally, the impact of national and organisational cultures on FSC is analysed, emphasising the challenges posed by a multicultural workforce in standardising food safety practices. This article also provides a comparative analysis of FSC across various sectors, such as meat and dairy processing, identifying sector-specific challenges and best practices. In particular, high-risk sectors tend to exhibit a stronger FSC due to regulatory pressure, while other sectors struggle with issues like communication and employee ownership. The importance of integrating behavioural training with cultural considerations is underscored as a key strategy for sustaining a positive FSC. For maintaining a strong FSC, tailored approaches, which account for cultural and operational differences, are necessary for improving food safety outcomes. This comprehensive analysis provides valuable insights for industry professionals and policymakers, offering a foundation for future research and the development of more effective food safety management practices.